Extragonadal germ cell tumor presenting with spinal cord compression: a case report and literature review - Roula A. Farah; Judy K. Matta; Aida A. Metri; Noha A. Bejjani-Doueihy; Ibrahim C. Saikali (SpringerOpen, 2022)
Abstract Background Yolk sac tumor or endodermal sinus tumor is an uncommon malignant germ cell neoplasm. This tumor usually presents in childhood or young adulthood as a testicular or ovarian mass. Extragonadal sites such as mediastinal, intracranial, and sacrococcygeal have been described. A review of the literature revealed limited related cases. The clinical presentation, radiographic characteristics, operative findings, and patient outcomes are discussed. Case presentation We report the occurrence of a primary paraspinal germ cell tumor in a 28-month-old boy who presented with thoracic spinal cord compression. The patient presented with pain, weakness, paraplegia, and bowel and bladder disturbances. MRI was done and showed a retroperitoneal and paravertebral mass invading the left diaphragmatic crus, the lateral neural foramen, and the posterior paravertebral muscles. Morphologic and immunohistochemical features were consistent with a germ cell tumor, namely an endodermal sinus tumor (yolk sac) of the epidural area. The final diagnosis was determined to be stage IV extragonadal germ cell tumor. The patient underwent emergency surgery consisting of T10-12 laminectomy and epidural mass resection with the release of the spinal cord compression and received chemotherapy consisting of cisplatin, bleomycin, and etoposide. After six cycles of chemotherapy, follow-up MRI showed complete resolution of the tumor. The patient has been in complete remission 16 years from his initial diagnosis. He still, however, has mild residual weakness in both lower extremities and some detrusor-sphincter dyssynergia. Conclusion Extragonadal germ cell tumors presenting with spinal cord compression are rare; however, they should be included in the differential diagnosis of every child younger than 3 years old who does not present with the typical features. Germ cell tumors are sensitive to platinum-based chemotherapy, and surgery should only be performed for spinal cord compression and for obtaining tissue biopsy for a definitive diagnosis. The sooner the decompression is done, the better neurological outcome is achieved. Long-term remission, and possibly cure, can be achieved with a multidisciplinary treatment strategy.